Kualitas Layanan Bidang Penempatan Kerja dalam Meningkatkan Kepuasan Masyarakat pada Dinas Tenaga Kerja Kota Banjarmasin - Kharunnisa Khairunnisa (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
Problem Formulation in this research are indicates that How quality of service bidang Penempatan Tenaga Kerja on Dinas Tenaga Kerja Kota Banjarmasin consist of tangible, reliability, responsiveness, assurance and empathy up grade social satisfaction. Kind data concists of quantitative data and qualitative data. Source data consist of prymary data and secondary data. Draft this research according to method using survey research is collection of data only done for in part of population. Population and sample this research amount 150 respondents. Technique collected data among them Field research are questionnairy, interview, observation, documentation and library research. Technique data analysis be explained in descriptive with quantitative is statistics method to used for describe of data collected.